Perbaikan Teknik Kultur Embrio Kelapa Kopyor (Cocos nucifera L.) Asal Sumenep Jawa Timur Melalui Penambahan Bahan Aditif dan Pengujian Periode Subkultur - , Sukendah; , Sudarsono; , Witjaksono; Nurul Khumaida (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
The success of culturing of "Kopyor" coconut (matured coconut with broken meat particles due to abnormal formation of endosperm) through embryo culture depends on the medium used.  A revised protocol on medium embryo culture was done to increase embryo germination and plantlet production of kopyor coconut obtained from Sumenep.  Embryos excised from mature nuts were cultured in solid Eeuwens basal media supplemented with 150 ml coconut water, 150 ml coconut milk, 50 mg/l thio-urea, and 100 mg/l thio-urea. Germinating embryos were transferred to solid Eeuwens basal media containing 100, 150, and 200 ml/l coconut water.  Subsequent transfers of the germinating embryos to fresh media to complete seedling development were done at different periods of subculture, i.e., 1, 2, 3, and 4 months. The highest viability of kopyor embryo was shown by 150 ml/l coconut water, about 95% embryos in this medium germinated. At plantlet phase, addition of coconut water did not give a positive result to the growth of kopyor plantlets.  However, coconut water could increase the complete plantlet, i.e., plantlet with shoot and good root. Growth and number of kopyor plantlets obtained were the best when the plantlets transferred into fresh medium every 2 months.   Key words:  Embryo culture, kopyor coconut, additive agents, period of subculture